Analysis Technological, Pedagogical And Content Knowledge (TPACK) Competency of SKI Teachers at MAN 2 Model Medan - Nurhaliza, Siti; Nasution, Wahyudin Nur; Fibri Rakhmawati (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The world is currently in turmoil is in the 4.0 era, meaning the world is in a heyday to sophistication technology. Development increasingly technology fast possible potential to all aspect including in the world of education. Everything that smells renewal naturally own possible impact to direction positive and also negative. Everything depends to individual each of them. is change That used to good direction or No. If done to good direction so naturally change the worth positive. Vice versa, if done to negative direction , then neither did the results obtained Good . Teachers are considered as someone who is perfect, p This because the teacher is considered as a person of merit in make somebody so that become success . In writing study This researcher use method nature research qualitative. Study qualitative nature to collection information with forms of data and documents as supporter facts on the ground. Result of study This show that the CK ability of the teachers at MAN 2 Model Medan is already OK, the PK skills of the SKI teachers at MAN 2 Model Medan are also good enter to good category, temporary Kindergarten abilities of SKI teachers in MAN 2 Model Medan are still Not yet Good. This matter seen from response students who feel bored in learning. The way it should be need improved returned by the teachers viz enhancement in control Technology and its applications in learning. This matter aim For makes it easier in delivery teaching materials and make it easy in reach objective learning.